2000
DOI: 10.1055/s-0042-1748040
|View full text |Cite
|
Sign up to set email alerts
|

Psychoacoustic Measures of Tinnitus

Abstract: This report reviews research from the 1930s to the present that has extended our understanding by investigating the characteristics of tinnitus that can be studied using psychoacoustic techniques. Studies of tinnitus masking and residual inhibition began in the 1970s, leading to the therapeutic use of tinnitus masking and a consequent increase in research devoted to tinnitus measurement. In 1981, the CIBA Foundation symposium on tinnitus advocated general adoption of four tinnitus measures: (1) pitch, (2) loud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(47 citation statements)
references
References 72 publications
(107 reference statements)
4
39
0
2
Order By: Relevance
“…In our study, evaluation of the tinnitus sound matching degree served as an indicator for patients need to be tested before customizing the music. As our tinnitus matching technique is strictly protocolized during the customization of patient-specific tinnitus characteristics in reference to their own subjective perception of tinnitus sounds; subsequently, as studies have validated that the therapeutic sound most similar to patient's tinnitus can be beneficial, we believe that our results are in line with our studies [7]. Due to the diversity and complexity of subjective tinnitus sounds, there are some patients whose tinnitus sounds would not match any of the existing edited sound fragments (as in group B) in all 4 steps of the matching test process.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In our study, evaluation of the tinnitus sound matching degree served as an indicator for patients need to be tested before customizing the music. As our tinnitus matching technique is strictly protocolized during the customization of patient-specific tinnitus characteristics in reference to their own subjective perception of tinnitus sounds; subsequently, as studies have validated that the therapeutic sound most similar to patient's tinnitus can be beneficial, we believe that our results are in line with our studies [7]. Due to the diversity and complexity of subjective tinnitus sounds, there are some patients whose tinnitus sounds would not match any of the existing edited sound fragments (as in group B) in all 4 steps of the matching test process.…”
Section: Discussionsupporting
confidence: 81%
“…While customizing personalized therapeutic sounds, the tinnitus sound matching is oftentimes considered as a critical reference factor [7]. However, we found that the customized sound could not match the tinnitus sound of some patients during sound therapy, and the customized sound therapy effect of these patients remains inconclusive.…”
Section: Introductionmentioning
confidence: 92%
“…The pitch-matched stimulus was presented at their comfort levels, and loudness was adjusted in small steps until the subjects stated that the loudness was identical to their tinnitus loudness. 16 Narrow-band noise was used as a masking sound stimulus, and the minimum masking level (MML) was determined based on the level at which subjects indicated that the tinnitus is no longer detectable. RI was determined at the level of MML+10 dB presented for 60 seconds 16 , 17 and was recorded as complete, partial, and negative based on the post-masking effect.…”
Section: Methodsmentioning
confidence: 99%
“… 16 Narrow-band noise was used as a masking sound stimulus, and the minimum masking level (MML) was determined based on the level at which subjects indicated that the tinnitus is no longer detectable. RI was determined at the level of MML+10 dB presented for 60 seconds 16 , 17 and was recorded as complete, partial, and negative based on the post-masking effect.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation